ENGAGEMENT IN ADVANCE CARE PLANNING: DO REGION-WIDE INTERVENTIONS WORK?. Issue 2 (1st June 2013) - Tayler, C; Hanvey, L; Teixeira, A A; Barwich, D; Baxter, S; Heyland, D K
Abstract : Background: Prior research suggests that only a small percentage of the general population is involved in ACP. Aim: To compare engagement in ACP among the general population of Canadian adults with the engagement among adults in a health authority with a region-wide ACP engagement initiative (Fraser Health (FH), British Columbia). Methods: An on-line opinion poll of a nationally representative sample of 1523 respondents including five questions regarding core ACP activities. Pearson χ 2 tests were used to compare the prevalence of ACP in FH and the rest of Canada. Results: Compared to the rest of Canada, respondents from FH had higher levels of ACP awareness (20% against 15%, p=0.025) and higher rates of ACP discussions with family and friends (59% against 51%, p=0.004). However, they had lower rates of written ACPs (15% against 20%, p=0.018). Discussion: The population of adults in FH tend to talk more with their family and friends about ACP than do adults in the rest of Canada. The fact that a lower number of respondents had written ACPs in FH could be explained by the fact that while FH had engaged professionals and the public around ACP, legislation supporting ACP was only recently declared. Conclusion: Engagement with the public by a health authority makes a difference in the levels of ACP awareness and discussions with family and friends. However, regulatory frames need to be in place in order to provide optimal support to ACP interventions.